Three-axis forces and torque sensor - Młotek, Paweł; Mynarek, Piotr; Kowol, Marcin (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper describes research on a prototype of a multi-axis force and torque sensor dedicated to the support system of a telescopic camera crane arm. Based on studies conducted on an actual telescopic camera crane arm, the requirements that the sensor must meet to enable precise control of the drives in two working axes of the telescopic camera crane arm were defined. In the sensor developed, a method for measuring forces and torques using an optical displacement sensor was proposed. A simplified sensor prototype was made to verify the assumptions, and measurement tests were carried out. Additionally, the paper presents a CAD model of the sensor using an elastic pin, based on which a numerical model was developed, and calculations of displacements and mechanical stresses were performed.